Progesterone receptor membrane component 1 (PGRMC1) expression in canine mammary tumors: A preliminary study - Terzaghi, Laura; Banco, Barbara; Groppetti, Debora; Dall'Acqua, Priscila C. [UNESP]; Giudice, Chiara; Pecile, Alessandro; Grieco, Valeria; Lodde, Valentina; Luciano, Alberto M. (Elsevier, 2020)
Canine mammary tumors (CMT) represent the most common neoplasms in female dogs and their diagnosis and classification relies on histopathological examination. Recently, PGRMC1 has been considered to be a putative biomarker for diagnosis and prognosis in many human cancers as it is expressed in a wide variety of tumors. This study represents the first description of PGRMC1 expression in CMT. PGRMC1 expression was initially assessed by immunohistochemistry in healthy or hyperplastic tissues and in four major histopathological types of CMT: simple and complex adenomas and carcinomas. PGRMC1 staining was represented by a scoring system that considered the percentage of positive cells and staining intensity. PGRMC1 expression was defined as either weak, moderate or strong. In healthy and hyperplastic tissues almost 100% of the epithelial cells stained intensely for PGRMC1. Adenomas showed similar features but with a more variable intensity. In tubular areas of adenocarcinomas, a lower percentage of epithelial cells (30–60%) stained for PGRMC1 with a weak intensity. Both the percentage of cells and intensity of PGRMC1 staining became progressively negative in the solid parts of the tumor. Western blot analysis of healthy and neoplastic mammary tissue (carcinomas samples) revealed the presence of the 25 kDa PGRMC1 band in both types of tissue, while the 50 kDa form was mainly detected in the healthy counterpart. This study reveals that PGRMC1 is expressed in CMT and its expression pattern changes depending on the pattern of growth of CMT. Further studies are now needed to determine PGRMC1's putative role and usefulness for typing and prognosis of different CMT subtypes.
Keywords: Cancer; Canine mammary Tumors; Immunohistochemistry; Mammary gland; PGRMC1